2007
DOI: 10.1002/pssc.200673242
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic effects in nonlinear optical rectification in small semi‐parabolic quantum dots

Abstract: We study the effects of excitons in nonlinear optical rectification in one-dimensional semi-parabolic quantum dots. We consider the case that the electron and the hole are confined in semi-parabolic potential with the same oscillator frequency. We present approximate analytical results in the strong confinement regime and find a closed-form relation between the nonlinear optical rectification coefficient of an exciton in the structure and the corresponding coefficient when only one electron exists in the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Indeed, very large second-order nonlinear optical properties associated with ISBT such as the second harmonic generation (SHG) [3], the nonlinear optical rectification [4], and frequency down conversion [5], and third-order nonlinear optical properties such as the dc Kerr effect [6], third harmonic generation (THG) [7], and four-wave mixing [8] have been observed experimentally. Following these experimental observations, many theoretical studies related to the optical nonlinearities have also been performed [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, very large second-order nonlinear optical properties associated with ISBT such as the second harmonic generation (SHG) [3], the nonlinear optical rectification [4], and frequency down conversion [5], and third-order nonlinear optical properties such as the dc Kerr effect [6], third harmonic generation (THG) [7], and four-wave mixing [8] have been observed experimentally. Following these experimental observations, many theoretical studies related to the optical nonlinearities have also been performed [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The second-order nonlinear optical coefficients can be obtained by density matrix approach and perturbation expansion method [ 12 , 13 ]. The expression for the OR coefficient, within a two-level system approach, is given by [ 5 , 6 ] …”
Section: Theorymentioning
confidence: 99%
“…Recently, several authors [ 5 , 6 , 8 ] studied the effects of an exciton on the second-order nonlinear properties in one-dimensional semi-parabolic quantum dots. Using analytical approximate results, they showed that the excitonic effects enhance significantly the OR and SHG coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Among the nonlinear optical properties, more attention had been paid to the second-harmonic generation (SHG) [17][18][19][20][21][22][23][24][25][26] and optical rectification (OR) [23][24][25][26][27][28][29][30][31][32][33] coefficients. It is well known that these even-order nonlinear optical properties are only non-zero in asymmetric quantum systems.…”
Section: Introductionmentioning
confidence: 99%